Traumatic Brain Injury Following Military Deployment: Evaluation of Diagnosis and Cause of Injury. Issue 1 (January 2019) - Regasa, Lemma Ebssa; Agimi, Yll; Stout, Katharine C.
Abstract : Objective: To evaluate the prevalence of delayed traumatic brain injury (TBI) diagnosis and cause of injury that resulted in a TBI diagnosis after military deployment. Design: Medical record notes were reviewed in 2016 from a random sample of 1150 US military service members who had their first-time deployment in 2011 and likely sustained a TBI. Location and cause of the injury were extracted from the progress note for analysis. Participants and Setting: Active-duty US military service members who received an International Classification of Diseases, Ninth Revision code for a TBI diagnosis in a military facility. Main Outcome Measures: Presence of TBI, location of injury, cause of injury, and time of diagnosis with respect to deployment. Results: The odds of being diagnosed with a deployment-related TBI were 8 times higher during the first 4 weeks upon return from deployment than the subsequent 32 weeks. The likelihood of diagnosing a deployment-sustained TBI during weeks 5 to 32 was 2 times higher than during 33 to 76 weeks following return from deployment. The proportion of deployment-related TBI diagnoses decreased with time following return from deployment but remained above 40% during weeks 33 to 76. Service branch, gender, race, occupation, and time between TBI diagnosis and return from deployment were significant predictors of deployment-related TBIs. Moving motor vehicle, sports, parachute, and being struck by objects were the top causes of injury in garrison (nondeployed setting), whereas blast produced the majority (66%) of all causes of injuries that resulted in a TBI in the deployed setting. Conclusion: The increased incidence rate of a TBI diagnosis following deployment can be attributed to delayed diagnosis of TBI sustained from injuries during deployment. TBIs sustained during deployment can be diagnosed beyond the initial 4 weeks after return from deployment and may continue up to 76 weeks following return from deployment.